Kompleksowe postępowanie fizjoterapeutyczne w skręceniu stawu skokowego - Paulina Brzezińska; Jan Paweł Mieszkowski (Kazimierz Wielki University, 2015)
Brzezińska Paulina, Mieszkowski Jan. Kompleksowe postępowanie fizjoterapeutyczne w skręceniu stawu skokowego = Comprehensive physiotherapy treatment methods in ankle sprains. Journal of Education, Health and Sport. 2015;5(9):527-548. ISSN 2391-8306. DOI10.5281/zenodo.31464 http://dx.doi.org/10.5281/zenodo.31464 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A527-548 https://pbn.nauka.gov.pl/works/635044 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.08.2015. Revised 05.09.2015. Accepted: 27.09.2015.   Kompleksowe postępowanie fizjoterapeutyczne w skręceniu stawu skokowego Comprehensive physiotherapy treatment methods in ankle sprains   Paulina Brzezińska1, Jan Mieszkowski2   1Uniwersytet Medyczny im. Karola Marcinkowskiego w Poznaniu 2Uniwersytet Kazimierza Wielkiego w Bydgoszczy   Słowa kluczowe: skręcenie stawu skokowego, badanie RTG, fizjoterapia.   Keywords: ankle sprain, X-ray, physiotherapy.   Autor do korespondencji: Paulina Brzezińska e-mail: brzezinskapp@gmail.com   Streszczenie Wstęp: Skręcenia stawu skokowego zaliczane są do jednych z najczęściej spotykanych urazów kończyn dolnych. Pomimo częstości występowania, nadal wielokrotnie są one lekceważone, zarówno w aspekcie wczesnej i prawidłowej diagnostyki medycznej jak i zastosowania szybkiego i optymalnego postępowania leczniczego. Cel pracy: Usystematyzowanie wiedzy na temat postępowania terapeutycznego, u osób po urazie stawu skokowego. Wnioski: W postępowaniu terapeutycznym u  osób po urazie stawu skokowego najważniejszą rolę odgrywa diagnostyka radiologiczna oraz kliniczna pozwalająca                    na postawienie właściwej diagnozy oraz na kreślenie celów terapii. Kompleksowe postępowanie fizjoterapeutyczne wpływa istotnie na skrócenie czasu koniecznego                          do przywrócenia możliwego do osiągnięcia poziomu funkcjonalnego pacjentów i zwiększa skuteczność stosowanych terapii.   Summary Introduction: Ankle sprains are classified as one of the most common injuries of the lower extremities.  This type of inquiry is still frequently underestimated, both in terms of early and proper medical diagnosis and the use of fast and optimal therapeutic management. Aim: Systematization of knowledge relating to the treatment of the ankle injuries, and analyze the therapeutic treatment and its effectiveness in the ankle sprains. Conclusions: Radiological and clinical diagnosis plays a key role in a normal therapeutic procedure for a person after ankle injury. It allows for diagnose and sets a objectives hierarchy for the optimized therapy. Comprehensive physiotherapy have a significant impact on the functional state of patients with ankle sprains significantly. increasing effectiveness of therapy.